A Plant Extract of Ribes nigrum folium Possesses Anti-Influenza Virus Activity In Vitro and In Vivo by Preventing Virus Entry to Host Cells - Ehrhardt, Christina (Public Library of Science, 2013)
Infections with influenza A viruses (IAV) are still amongst the major causes of highly contagious severe respiratory diseases not only bearing a devastating effect to human health, but also significantly impact the economy. Besides vaccination that represents the best option to protect from IAV infections, only two classes of anti-influenza drugs, inhibitors of the M2 ion channel and the neuraminidase, often causing resistant IAV variants have been approved. That is why the need for effective and amply available antivirals against IAV is of high priority. Here we introduce LADANIA067 from the leaves of the wild black currant (Ribes nigrum folium) as a potent compound against IAV infections in vitro and in vivo. LADANIA067 treatment resulted in a reduction of progeny virus titers in cell cultures infected with prototype avian and human influenza virus strains of different subtypes. At the effective dose of 100 µg/ml the extract did not exhibit apparent harming effects on cell viability, metabolism or proliferation. Further, viruses showed no tendency to develop resistance to LADANIA067 when compared to amantadine that resulted in the generation of resistant variants after only a few passages. On a molecular basis the protective effect of LADANIA067 appears to be mainly due to interference with virus internalisation. In the mouse infection model LADANIA067 treatment reduces progeny virus titers in the lung upon intranasal application. In conclusion, an extract from the leaves of the wild black currant might be a promising source for the development of new antiviral compounds to fight IAV infections.